A European social union after the crisis / edited by Frank Vandenbroucke, University of Amsterdam, Catherine Barnard, University of Cambridge, Geert De Baere, University of Leuven. - Vandenbroucke, Frank, 1955-; Barnard, Catherine; Baere, G. de (Cambridge University Press, 2017)
Today, many people agree that the EU lacks solidarity and needs a social dimension. This debate is not new, but until now the notion of a 'social Europe' remained vague and elusive. To make progress, we need a coherent conception of the reasons behind, and the agenda for, not a 'social Europe', but a new idea: a European Social Union. We must motivate, define, and demarcate an appropriate notion of European solidarity. We must also understand the legal and political obstacles, and how these can be tacked. In short, we need unequivocal answers to questions of why, what, and how: on that basis, we can define a clear-cut normative and institutional concept. That is the remit of this book: it provides an in-depth interdisciplinary examination of the rationale and the feasibility of a European Social Union. Outstanding scholars and top-level practitioners reflect on obstacles and solutions, from an economic, social, philosophical, legal, and political perspective.